ANALISIS PENGGUNAAN ALAT PELINDUNG DIRI SEBAGAI ANTISIPASI KECELAKAAN KERJA PADA KARYAWAN BAGIAN PRODUKSI DI SENTRA INDUSTRI MEBEL DESA SERENAN - Khoirunisa, Asahra; Johar, Syefira Ayudia; Ani, Nur (Jurnal Ilmu Kesehatan Masyarakat Berkala (JIKeMB), 2025)
Background: The use of Personal Protective Equipment (PPE) at the Serenan Village Furniture Industry Center is still low, although it is important to prevent work accidents. Based on data from BPJS Employment 2023 and Permenaker No. 8 in 2010, many accidents were caused by negligence in the use of PPE. Early observations show that only 30% of workers use it. Method: This research uses qualitative methods with interviews, observation, and documentation techniques for 12 production and finishing workers. The results show a low management commitment to work safety, limited availability of PPE, and weak socialization and supervision. The main obstacles include uncomfortable PPE, a lack of habits, and the absence of strict sanctions. Conclusion, the use of PPE has not been optimal. It is necessary to increase management commitment, adequate provision of PPE, as well as continuous socialization and supervision. Keywords: Compliance, Furniture Industry, Occupational Safety, Personal Protective Equipment, Risk management